PEMANFAATAN TULANG SEBAGAI ARTEFAK DARI SITUS GUA KIDANG BLORA JAWA TENGAH KOLEKSI BALAR YOGYAKARTA - Angello Winarko, Michael (Humanis; Volume 9. No. 2. November 2014)
The substance of this research is to discuss about the animal bones used as tools from the site of Kidang Blora Cave as the excavation result of Archaeological Centre of Yogyakarta. The objective of this research is to find out the forms, functions, types of bones, types of animals and their habitats in the past. This research is expected to be able to provide contribution for science development in the field of archaeology, mainly on bone tools as one of the artefacts in archaeological world.
Keywords: Kidang Blora Cave, bone, tool.